2017
DOI: 10.18240/ijo.2017.04.19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative optical quality according to the degree of decentering of V4c implantable collamer lens

Abstract: Our results suggest that Hole ICL implantation provides satisfactory visual quality that is equivalent to that provided by conventional ICL, regardless of the presence of central hole and degree of decentering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Pérez-Vives [ 18 , 19 ] reported the results of an ICL decentration simulation test in vitro, and found that coma was directly correlated with the decentration value of the ICL and increased more with pupil diameter and higher refractive degree. Our study showed that tilt and decentration had no significant effect on postoperative aberrations, and had no significant correlation with postoperative UDVA and CDVA after adjusting for age, eye, preoperative refraction, and preoperative scotopic pupil, which is consistent with the results of Park [ 27 ]. Additionally, the effect of ICL decentration and tilt on postoperative visual acuity would be clinically insignificant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pérez-Vives [ 18 , 19 ] reported the results of an ICL decentration simulation test in vitro, and found that coma was directly correlated with the decentration value of the ICL and increased more with pupil diameter and higher refractive degree. Our study showed that tilt and decentration had no significant effect on postoperative aberrations, and had no significant correlation with postoperative UDVA and CDVA after adjusting for age, eye, preoperative refraction, and preoperative scotopic pupil, which is consistent with the results of Park [ 27 ]. Additionally, the effect of ICL decentration and tilt on postoperative visual acuity would be clinically insignificant.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with these values, our findings are relatively lower; this discrepancy may be attributed to the location of the ICL haptics on the ciliary sulcus, which allows more stability and less influence from the suspensory ligament and other structures [ 26 ]. A study of ICL that used the pupil center as the reference, reported that decentration of 48.9% and 93.6% of eyes were within 0.36 mm and 0.72 mm after ICL implantation, respectively [ 27 ]. Notably, the selection criteria of the reference axis remain ununified.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [ 13 ] used the KR-1 W aberrometer to measure the optical quality of eyes implanted with the V4c and the non-hole model at different degrees of decentering. Table 2 shows data on centered lenses for a 4.0-mm pupil in 46 eyes with a mean preoperative SE of − 8.58 ± 2.08 D. Mean HOAs value was similar to that found by Shimizu et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [ 13 ] measured 46 eyes (centered lenses with a mean SE of − 8.58 ± 2.08 D) with the same instrument at the same follow-up, reporting similar outcomes: 33.42 ± 9.20 cpd and 0.19 ± 0.06. They compared these values with those found in 49 eyes implanted with the non-hole ICL and showed that they were not significantly different between both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation